Transformative Da'wah Strategy of Women Ulema in the Issue of Bullying in Pesantren: An Action Study of the Nawaning Nusantara Agency - Najiha, Rina; Umam, Fawaizul; Matkur, Matkur (West Science Social and Humanities Studies, 2026)
Cases of bullying in Islamic boarding schools continue to occur, while traditional approaches centered on patriarchal authority figures and punitive punishment have proven inadequate. This descriptive qualitative research analyzes transformative da'wah strategies and young women's ulama agencies, which are members of the Nawaning Nusantara network, in responding to the violence. Data collection was carried out through digital discourse analysis, literature studies, and document reviews of religious views, which were then analyzed using the theoretical framework of Agency and Transformative Da'wah. The results of the study show that Nawaning Nusantara dismantles the asymmetrical hierarchy of power through three main intervention areas: (1) an epistemological approach by reinterpreting classical texts based on the principle of the protection of the soul (hifdz al-nafs); (2) institutional stages through the establishment of safe spaces and the integration of victim-centered psychological approaches; and (3) cultural deconstruction through mental health literacy campaigns in the digital space. In conclusion, the agency of women clerics succeeded in recontextualizing religious traditions into instruments of liberation, changing the paradigm of conflict resolution from saving institutional reputations to fulfilling the rights of survivors. This model of restorative justice proves the intrinsic capacity of Islamic boarding schools to reform their system in a humane manner, so it is recommended to be adopted as a macro standard for child protection.